EVALUASI LANGGANAN LISTRIK FAKULTAS KESEHATAN MASYARAKAT UNIVERSITAS DIPONEGORO SEMARANG - Ketut Budiman; Achmad solichan; - Karnoto (PSTE UNIMUS, 2012)
Energy is one important part of everyday life, especially electrical energy . Electrical energy must be consider the level of economic needs, so that the availability of electrical energy in accordance with thus the availability of electricity and energy fuel for power supply is very limited as a result of the energy crisis . People should be selective in the use of electrical energy for daily life in order to save in financial terms as well as the availability of energy sources. The aims of this research is to analyze of electrical load in Faculty of Public Health, Diponegoro University based on their need alignment with their subscription. The results obtained when the subscription faculty of public health is still a need in raised it to 315 KVA, and if they wantto subscribe 240 KVA.Keywords: evaluation Subscription,